Metonymy in Motion: How Metonymy Shapes Soccer Narratives and Enhances ELT Practices - Juliana, Juliana; Mulyadi , Mulyadi (Elsya : Journal of English Language Studies, 2025)
This study addresses a critical gap in sports linguistics by exploring the cognitive semantic role of metonymy in digital soccer journalism, an area that remains underexamined despite its pervasive use in media discourse. Using a corpus-based cognitive semantic approach, this qualitative study examines the prevalence and patterns of metonymy in soccer news articles published on Goal.com. A purposive sampling technique was employed to select 250 news articles collected from August 2021 to May 2024, providing a robust dataset for analysis. The findings reveal that "whole for part" metonymy dominates, where teams, leagues, or nations substitute for individual players or components, reinforcing collective identity and aligning with readers’ cognitive schemas. Metonymic collocations also exhibit consistent patterns, with renowned teams and leagues frequently serving as proxies for players and events, demonstrating a cognitive preference for associating collective entities with their constituents. These results highlight metonymy’s role in simplifying narratives, enhancing audience engagement, and shaping cultural representations in digital sports media. Beyond its linguistic significance, this study contributes to English Language Teaching (ELT) by demonstrating how metonymy-based corpus analysis fosters critical reading, discourse analysis, and media literacy. Sports journalism serves as an engaging pedagogical resource for teaching pragmatic competence and lexical awareness, helping learners decode implicit meanings and cognitive framing. By showcasing metonymy’s role in narrative efficiency and cognitive engagement, this study underscores its broader implications for media studies, cognitive linguistics, sports journalism, and ELT.